Assessing the Adsorption of Bipyridinium Herbicides on Model Soil Granular Media - Tadeo-Jalife, Nahim R.; Vasquez-Medrano, Ruben; Quevedo, Ivan R. (Frontiers in Water, 2021)
In this research work, the adsorption of two bipyridinium herbicides (i.e., Diquat, and Paraquat) on natural soil and on model soil surfaces has been studied at different water chemistries commonly found in the environment (e.g., pH, supporting electrolyte, and presence of humic or fulvic acids). The experimental work was carried out in the laboratory, using experimental batches of clean quartz sand, silanized quartz sand and sandy soil as a model of agricultural topsoil where herbicides are commonly used and can be adsorbed. The concentrations reached at the equilibrium were analyzed by UV-Visible Spectroscopy for the supernatant fraction of the samples. The concentrations were fitted using adsorption isotherms to determine the adsorption mechanisms (i.e, chemisorption or physisorption) at the interface. In general terms, we have encountered that the nature of the soil matrix plays an important role on the study of pollutant adsorption. In experiments carried out on silica sand, the most abundant component of the natural soil matrix, no significant sorption was observed (<1.5 mg/g) for any of the herbicides. Yet, in experiments carried out on the presence of clay and natural organic matter (i.e., fulvic and humic acids), the adsorption of both herbicides is much higher, likely due to the chemical structure of the molecules that might facilitate the complexation with both herbicides. This investigation improves our understanding of the role that soil granular components play on the absorption of two commonly used herbicides and adequately predict their fate in natural aquatic environments.